Kajian Berbagai Lama Penyimpanan Entres Terhadap Hasil Sambung Sampin Gkakao (Theobroma Cacao L.) Klon Sulawesi - Yuldanto Larekeng; Sakka Samudin; Hendry Barus (Universitas Tadulako, 2017)
The purpose of this research was to determine the effect of scionsstored under various time periods on side-cleft grafting results at cacao plant. The research used a Randomized Block design in which five storage period treatments were applied including no period of storage (control), 3 d, 6 d, 9 d, and 12 d storage periodsafter scion cutting time. Each treatment was replicated five times resulting in 25 experimental units. Variables observed were the percentage of living graftings, number of buds, length of buds and total leaf number of scions. The research results showed that under 9 d and 12 d storage periods after scion cutting time, the percentage of living graftings was 53.59% and 36.41%, respectively, while much higher percentage were found in the control, 3 d, and 6 d treatments which were 79.38%, 79.38% and 70.78%, respectively. The control, 3 d and 6 d storage period treatments were significantly affected the percentage of living scion and bud length at 30 d and 45 d after grafting. Scions can be stored up to 6 d after cutting which support a well growth of side-cleft grafting cacao.